Analisa Stopping Sets Pada Internet-Of-Things (IoT) Berkemampuan Multi User Detection (MUD) Dengan Panjang Blok Terbatas - Muhammad Rifqy Asrul; Yusnita Rahayu; Khoirul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
By increasing number of users / devices, the Coded Random Access application is suitable for use enable wireless access successfully in super congested networks. Usage problems Coded Random Access prohibitions emerged. Stop sets are dangerous structures, where none exist another way for multiple users stuck in a set to be decoded. Set stop by degree distribution. This paper presents a probability analysis of the stopping set coded random Access to Internet of Thing (IoT) with Multi User Detection (MUD) capability. It uses MATLAB R2016a as a proving tool. The result of this research is used as an assessment of future IoT network performance. The result is done that this research has a high chance of being accurate and very practical. Then, a new graph stopping set for MUD with a constant 2 is found in the simulation results. Number of user / device randperm, ˄ (x) and G affect the probability of the set out of the CRA for IoT networks. The higher the G value, the higher the probability that the number of set stops will occur. Keywords: Coded Random Access, Multi User Detection, Stopping Sets, Internet-of-Things